Effect Of Mental Workload And Moral Sensitivity On Nurse Performance In The Acute Inpatient Room Of The Prof. Dr. M. Ildrem Mental Hospital, Medan - Esther Simatupang; Siti Saidah Nasution; Elmeida Effendy; Roy Wilson Sihaloho (International Journal of Medicine and Health, 2024)
Objectives: High mental workload can decrease nurse performance. Nurses with higher moral sensitivity are ethically more practicing professionals and the quality of care is better. This study assesses effect of Mental Workload and Moral Sensitivity on Nurse Performance in the Acute Inpatient Room of the Prof. Dr. M. Idrelm Mental Hospital Medan in Indonesia . Methods: The study used a cross-sectional design, sampel number of 58 nurses in acutel inpatient room through total sampling. NASA-TLX Questionnaires for Mental Workload, Moral Sensitivity Questionnaires for Moral Sensitivity and Individual Work Performance Questionnaires for Nurse Performance. Analyzed data using the Statistical Package for social Science (SPSS) version 26 software. Descriptive statistics, Pearson test and multiple linear regression analysis to measure its effect. A p-vaule of < 0.05 was considered statistically significant at a 95% confidence level. Result: Majority of participant had a high level of mental workload (86.2%), high level of moral sensitivity (58.6%) and had good level of performance (53.4%). Further, there is no correlation mental workload with nurses performance (p = 0.350), but moral sensitivity significantly correlated with nurses performance (p = 0.041). Conclusion: Nurse has level mental workload high indicate prone to fatique and burnout, but they have good performance because they have adapted to the existing work situation. This is supported by high moral sensitivity so that nurses feel very responsible for their profession.